2017
DOI: 10.15537/smj.2017.8.20393
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for enteral feeding intolerance screening in critically ill patients

Abstract: Objectives:To identify risk factors for enteral feeding intolerance screening in critically ill patients, thereby, provide some reference for healthcare staff to assess the risk of feeding intolerance, and lay the foundation for future scale development.Methods:This study used a mixed methodology, including a literature review, semi-structured interviews, the Delphi technique, and the analytic hierarchy process. We used the literature review and semi-structured interviews (n=22) to draft a preliminarily item p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Patient status (e.g., injury severity score, multiple organ dysfunction score), general conditions (e.g., abdominal surgery), and GI function (e.g., acute gastrointestinal injury grade), as well as biochemical indexes and treatment measures, should be considered as they represent potential risk factors for feeding intolerance. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Patient status (e.g., injury severity score, multiple organ dysfunction score), general conditions (e.g., abdominal surgery), and GI function (e.g., acute gastrointestinal injury grade), as well as biochemical indexes and treatment measures, should be considered as they represent potential risk factors for feeding intolerance. 28 …”
Section: Discussionmentioning
confidence: 99%
“…After composite resection and free flap reconstruction, patients are admitted to intensive care units (ICUs) in order to allow for the close monitoring of flap and respiratory status [ 7 ]. These patients present with a number of risk factors that aggravate feeding intolerance, including postoperative status, prolonged bed ridden immobility, decreased head elevation (less than 30 °), mechanical ventilation, and the customary use of sedative agents [ 8 ]. Feeding intolerance is common in postoperative critically ill patients, and is conventionally related to poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of intestinal nutritional intolerance has yet to be fully explored. Possible mechanisms underlying intolerance to EN feeding include gastrointestinal nerve and smooth muscle injuries, inflammation, surgery, opioid use, electrolyte disturbance, and hyperglycemia (8,12). However, studies on the relevant risk factors are still controversial (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms underlying intolerance to EN feeding include gastrointestinal nerve and smooth muscle injuries, inflammation, surgery, opioid use, electrolyte disturbance, and hyperglycemia (8,12). However, studies on the relevant risk factors are still controversial (7,12). Arabi et al (13) suggested that when EN is carried out for severe patients treated with vasopressors, attention must be paid to the occurrence of lactic acidosis, which may be an important indicator of parenteral ischemia.…”
Section: Introductionmentioning
confidence: 99%